REKONSTRUKSI KONSEP INOVASI PENDIDIKAN ISLAM BERBASIS DESIGN THINKING DAN NILAI ISLAMI - Nilamsari Kusumawati Putri; Neni Sumarni; Difa Wijaya (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
Islamic education is currently confronted with the dual imperative of preserving its foundational theological values while simultaneously responding to the accelerating demands of contemporary society. Conventional approaches to educational innovation within Islamic institutions have frequently been criticized for their fragmented application and limited contextual sensitivity. This study aims to reconstruct the conceptual framework of Islamic educational innovation by integrating Design Thinking methodology with core Islamic values, producing a model that is simultaneously human-centered, process-driven, and spiritually grounded. Employing a systematic library research methodology, this study collects, critically examines, and synthesizes peer-reviewed journal articles, scholarly books, and authoritative educational documents published within the last five years. Content analysis and thematic analysis techniques guide the interpretive process. Findings demonstrate that the five stages of Design Thinking Empathize, Define, Ideate, Prototype, and Test can be organically aligned with Islamic epistemic principles such as mushahadah, tafakkur, ijtihad, tajribah, and taqwim, yielding a reconstructed innovation model that is both methodologically rigorous and Islamically authentic. This model offers a transformative pathway for Islamic educational institutions seeking sustainable, values-driven innovation.